Woman Becomes Goddess in Bollywood: Justice, Violence, and the Feminine in Popular Hindi Film - Erndl, Kathleen M. (The journal of religion and film, 2013)
What happens “when a woman becomes Chandika?” This essay contributes to an on-going discussion of the theme of “avenging women” in popular Indian cinema, with particular focus on the transformation of a woman into a fierce Goddess who avenges oppression and re-establishes justice. Analysis of the story line and selected song sequences from the Hindi language film Anjaam (“Outcome,” 1994) in light of themes from the Hindu Sanskrit text, the Devi-Mahatmya (“Greatness of the Goddess,” 5thc. C.E.) shows how traditional religious images and values are adapted and transformed in a modern context.